EFEKTIVITAS DAKWAH MELALUI PENGAJIAN RUTIN DI MUSHOLLA AL-HIDAYAH - Wijdan Alghifary, Mohamad Hapiz (Jurnal Dakwah Tabligh, 2023)
Regular recitals need to be held to provide religious guidance to the community at this time. This study uses a descriptive qualitative method which aims to reveal events or facts, circumstances, and phenomena that occurred during the research. Data collection techniques were carried out through observation, interviews, and documentation. While the validity of the data using source triangulation. The study aimed to determine the effectiveness of the da’wah process through routine recitations at the Al-Hidayah Mosque, as well as to determine the supporting and inhibiting factors of this program. The results of the study show that the existence of this routine recitation provides religious guidance and a positive impact on the congregation who attends. The supporting factors are the existence of a management organizational structure, the commitment of the congregation to the implementation of routine recitation, and the strategic location of the prayer room. The inhibiting factors include the large number of local people who work in companies or factories and the good and bad weather.